PENGARUH ASPEK EKONOMI SERTA PERAN PEMERINTAH TERHADAP KUALITAS LINGKUNGAN DI INDONESIA - Anggi Puspitasar; Dedy Yuliawan (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The purpose of this study was to analyze and obtain information on the extent to which economic aspects such as population density, GDP of the industrial sector, and the role of government affect environmental quality. This is reflected in the Environmental Budget for Environmental Quality (IKLH). The information used in this study covers 34 regions in Indonesia from 2018 to 2021. In this study, the least squares method (PLS) with model (FEM) was used. The results show that all three have a large impact on the variable IKLH. The fluctuating population density has a negative impact on Indonesia's environmental quality, while the fluctuating GRDP and environmental budget in the industrial sector have a positive impact.